Assessing the efficacy of an experimental strength and conditioning program for professional mixed martial arts athletes - Davidenko, I.; Bolotin, A.; Pronin, E.; Anisimov, M.; Petrov, V.; Vorozheikin, A.; Tyupa, P.; Melnichuk, A.; Kovalchuk, A.; Tyrina, M. (Journal of Physical Education and Sport, 2024)
High demands on the physical training are set before athletes-fighters engaged in professional MMA. Therefore, the development of new programs for the integrated development of strength and conditioning training in mixed martial arts is an urgent direction in the training process. Research aim: to experimentally substantiate and develop a training program aimed at developing strength and conditioning readiness for fights among professional MMA athletes. Materials and methods. 24 professional mixed martial arts fighters aged 26.1 ± 2.5 and with 8.4 ± 1.3 years of experience in this sport participated in the research. The athletes completed two different strength and conditioning training programs for 18 weeks. Group 1 (CG) studied according to the standard physical training methodology, group 2 (EG) studied according to the experimental program developed by us. In the program, the strength and conditioning training of professional mixed martial arts athletes is divided into two blocks - the off-season (preparatory period) and the training camp (competitive period). In the first block, the training program consisting of three consecutive mesocycles included exercises to develop aerobic ability, as well as maximum aerobic power and speed-strength qualities. The second block of the program incorporated specific plyometric, strength, and conditioning exercises, focusing on diverse barbell exercises bodyweight workouts. Rigorous assessments were conducted to evaluate athletes' strength, conditioning,physical performance, and technical and tactical preparedness. Results. Revealed a significant improvement in the experimental group's athletes compared to those in the control group across various indicators, including strength, conditioning abilities, physical performance, and technical and tactical qualities. Conclusions. The experimental program uses in professional mixed martial arts fighters revealed an increase in the values of strength endurance by 18% and maximum strength by 12%. A positive relationship between the characteristics of fighters` strength and conditioning training and technical and tactical indicators has been established. The fighters` activity increased by 19.9%, the technical and tactical actions effectiveness by 27.1%, the defensive actions reliability by 13.6%.